Resolusi Kandang Baterai untuk Meningkatkan Pendapatan Peternak Itik Tradisional Melalui Pemeliharaan Intensif - Supranoto, Supranoto; Suryoto, Suryoto; Tuswati, Sari Eko (Universitas Muhammadiyah Mataram, 2026)
Abstract: This community service program aimed to enhance the productivity and managerial skills of traditional duck farmers in Karanggintung Village, Banyumas Regency, specifically targeting the Mutiara Bir